Persistence of antibody response following a booster dose of Hib-MenC-TT glycoconjugate vaccine to five years: a follow-up study. - Khatami, A; Snape, MD; Wysocki, J; John, T; Westcar, S; Mesaros, N; Peddiraju, K; Boutriau, D; Yu, L; Pollard, A (2012)
BACKGROUND: Antibodies against Haemophilus influenzae type b (Hib) and serogroup C Neisseria meningitidis (MenC) persist better to 3½ years of age after a 12-month booster dose of a combination Hib-MenC glycoconjugate vaccine (Hib-MenC-TT) in children primed in infancy with Hib-MenC-TT and diphtheria-tetanus-acellular-pertussis-inactivated poliovirus vaccine (DTaP-IPV) than in those who received a monovalent MenC-CRM197 and DTaP-IPV-Hib (also TT conjugated). Pertussis antibodies against filamentous hemagglutinin and pertactin are higher at 5 and 12 months in children who received DTaP-IPV compared with those immunized with DTaP-IPV-Hib. We evaluated whether these differences persisted to later childhood, following a preschool booster of DTaP-IPV at 3½ years of age. METHODS: Children in the United Kingdom and Poland previously enrolled in the aforementioned randomized-controlled trial had a blood sample taken at 5 years of age. Antipolyribosylribitol phosphate (Hib) IgG and MenC bactericidal antibody (baby rabbit complement) titers were compared between those immunized in infancy (at 2, 3 and 4 months) with DTaP-IPV/Hib-MenC-TT (Hib-MenC-TT group) and those who received DTaP-IPV-Hib with a monovalent MenC-CRM197 (control group). Antibody concentrations against filamentous hemagglutinin, pertactin and pertussis toxin were also measured at this visit. RESULTS: Two hundred sixty-eight participants aged 58-64 months were enrolled. MenC baby rabbit complement titers ≥1:8 were seen in 115 of 194 of the Hib-MenC-TT group (59.3% [52.0-66.3%]) and 26 of 58 (44.8% [31.7-58.5%]) of control group participants. MenC baby rabbit complement geometric mean titers were 30.4 and 11.3, respectively (ratio 2.70 [1.55- .73]). Antipolyribosylribitol phosphate (Hib) IgG concentrations ≥ 1.0 μg/mL were seen in 171 of 197 (86.8% [81.3-91.2%]) of the Hib-MenC-TT group and 36 of 58 (62.1% [48.4-74.5%]) of control group participants. Antipolyribosylribitol phosphate IgG geometric mean concentrations (GMCs) were 3.82 and 1.67, respectively (ratio 2.29 [1.59-3.28]). Sixty-eight UK participants aged 58-63 months had sera analyzed for the pertussis antigens (44 DTaP-IPV recipients, 14 DTaP-IPV-Hib recipients). Antipertussis toxin IgG GMCs were similar for participants immunized with DTaP-IPV and DTaP-IPV-Hib: 8.2 EL.U/mL (6.1 - 10.9) compared with 7.2 EL.U/mL (3.9 - 13.4). Antifilamentous hemagglutinin IgG GMCs were higher for DTaP-IPV recipients (164.7 EL.U/mL [119.4-227.1]) compared with DTaP-IPV-Hib recipients (66.8 EL.U/mL [43.8-101.7]), as were antipertactin IgG GMCs: 102.8 EL.U/mL (67.1-157.3) compared with 23.4 EL.U/mL (15.1-36.2). CONCLUSION: Vaccines used for infant immunization against Hib and MenC differ in their ability to prime responses to a booster dose of Hib-MenC-TT, and this difference persists to at least 5 years of age. Persistence of antipertussis antibody following a preschool booster of DTaP-IPV is also influenced by immunizations received at 2, 3 and 4 months of age, underlining the importance of infant immune priming in the maintenance of antibody levels through childhood.